Subcarrier Resource Optimization for Cooperated Multipoint Transmission. (7th November 2010) - Zhang, Hui; Xu, Xiaodong; Li, Jingya; Tao, Xiaofeng
Abstract : The concept of Cooperated Multipoint (CoMP) transmission is proposed for LTE-Advanced, which is in a form of distributed networks. In this background, a novel CoMP architecture is proposed in this paper, based on Group Cell concept in China FuTURE 4G TDD systems. Moreover, four actual scenarios are also concluded in CoMP, which, respectively, are single user in intracell, multiple users in intracell, single user in intercell and slide handover in intercell. In addition, a joint subcarrier optimization method is proposed to mitigate the intercell interference and improve performance under CoMP architecture; the method includes two aspects, which, respectively, are subcarrier allocation with maximum gain to interference plus noise ratio (GINR) and power allocation based on balanced signal to interference plus noise ratio (SINR). On this basis, three combined schemes are presented in simulation. Compared with traditional scheme, the proposed scheme improves throughputs and reduces blocking probability. Moreover, the average data rates in cell edge are also raised.